The Barley HvWRKY6 Transcription Factor Is Required for Resistance Against Pyrenophora teres f. teres - Tamang, Prabin; Richards, Jonathan K.; Solanki, Shyam; Ameen, Gazala; Sharma Poudel, Roshan; Deka, Priyanka; Effertz, Karl; Clare, Shaun J.; Hegstad, Justin; Bezbaruah, Achintya; Li, Xuehui; Horsley, Richard D.; et al. (Frontiers in Genetics, 2021)
Barley is an important cereal crop worldwide because of its use in the brewing and distilling industry. However, adequate supplies of quality malting barley are threatened by global climate change due to drought in some regions and excess precipitation in others, which facilitates epidemics caused by fungal pathogens. The disease net form net blotch caused by the necrotrophic fungal pathogen Pyrenophora teres f. teres (Ptt) has emerged as a global threat to barley production and diverse populations of Ptt have shown a capacity to overcome deployed genetic resistances. The barley line CI5791 exhibits remarkably effective resistance to diverse Ptt isolates from around the world that maps to two major QTL on chromosomes 3H and 6H. To identify genes involved in this effective resistance, CI5791 seed were γ-irradiated and two mutants, designated CI5791-γ3 and CI5791-γ8, with compromised Ptt resistance were identified from an M2 population. Phenotyping of CI5791-γ3 and -γ8 × Heartland F2 populations showed three resistant to one susceptible segregation ratios and CI5791-γ3 × -γ8 F1 individuals were susceptible, thus these independent mutants are in a single allelic gene. Thirty-four homozygous mutant (susceptible) CI5791-γ3 × Heartland F2 individuals, representing 68 recombinant gametes, were genotyped via PCR genotype by sequencing. The data were used for single marker regression mapping placing the mutation on chromosome 3H within an approximate 75 cM interval encompassing the 3H CI5791 resistance QTL. Sequencing of the mutants and wild-type (WT) CI5791 genomic DNA following exome capture identified independent mutations of the HvWRKY6 transcription factor located on chromosome 3H at ∼50.7 cM, within the genetically delimited region. Post transcriptional gene silencing of HvWRKY6 in barley line CI5791 resulted in Ptt susceptibility, confirming that it functions in NFNB resistance, validating it as the gene underlying the mutant phenotypes. Allele analysis and transcript regulation of HvWRKY6 from resistant and susceptible lines revealed sequence identity and upregulation upon pathogen challenge in all genotypes analyzed, suggesting a conserved transcription factor is involved in the defense against the necrotrophic pathogen. We hypothesize that HvWRKY6 functions as a conserved signaling component of defense mechanisms that restricts Ptt growth in barley.